2016
DOI: 10.17126/joralres.2016.059
|View full text |Cite
|
Sign up to set email alerts
|

Influence of adaptation of removable partial denture on masticatory performance.

Abstract: Abstract:Objective: To compare the masticatory performance (MP) of patients with old removable partial denture (RPD), recently inserted RPD and already adapted RPD by means of the simple sieve test. Material and Methods: Twenty-nine adult (>18 years old) volunteer patients were recruited, with lower and upper RPD, excluding total edentulous subjects in the upper and lower jaw, with temporomandibular disorders, severe periodontal disease, mental disability or systemic disease compromising the masticatory or ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 26 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…These findings are supported by Nakouzi et al who also demonstrated that removable partial denture has a strong connection with masticatory ability due to their important role in restoring oral function and health following teeth loss. Thus, the use of dentures like the ones utilized herein may have a positive impact on patient satisfaction and quality of life [7,17].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These findings are supported by Nakouzi et al who also demonstrated that removable partial denture has a strong connection with masticatory ability due to their important role in restoring oral function and health following teeth loss. Thus, the use of dentures like the ones utilized herein may have a positive impact on patient satisfaction and quality of life [7,17].…”
Section: Discussionmentioning
confidence: 99%
“…There are many factors that influence the reason why the acrylic-made removable partial dentures that were made in the RSKGM FKG UI have not been able to restore the ability of mastication on the seventh day after the insertion of the denture, even though it was convenient to use. Work conducted by Nakouzi et al suggests that the average time for a person to adapt to removable partial dentures s about 32.5 days [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations